Serum soluble epoxide hydrolase related oxylipins and major depression in patients with type 2 diabetes. (April 2021) - Anita, Natasha Z.; Forkan, Nubaira; Kamal, Radia; Nguyen, Michelle M.; Yu, Di; Major-Orfao, Chelsi; Wong, Sophie K.; Lanctôt, Krista L.; Herrmann, Nathan; Oh, Paul I.; Shah, Baiju R.; Gilbert, Jeremy; et al.
Abstract: Background: People with type 2 diabetes mellitus (T2DM) are at increased risk for depression. Both conditions are associated with disturbances in polyunsaturated fatty acids. Omega-3 and omega-6 fatty acids can be converted into bioactive epoxides by cytochrome P450s (CYP450), which play pro-resolving roles in the inflammatory response; however, soluble epoxide hydrolase (sEH) metabolizes epoxides into diols, which lack pro-resolving functions and can be cytotoxic. Here, we survey serum CYP450- and sEH-derived metabolite concentrations in people with T2DM with and without a major depressive episode. Methods: Sunnybrook Type 2 Diabetes Study (NCT04455867) participants experiencing a major depressive episode (research version of the Structured Clinical Interview for DSM-5 criteria) were matched 1:1 for gender, glycosylated hemoglobin A1c and body mass index to participants without a current depressive episode. Depression severity was assessed using the Beck Depression Inventory 2nd Edition (BDI-II). From fasting morning blood, unesterified serum oxylipins were quantified by ultra-high-performance liquid chromatography tandem mass spectrometry following solid phase extraction, and interleukin-6 (IL-6) by enzyme-linked immunosorbent assay. Results: Between 20 depressed and 20 non-depressed participants (mean age 58.9 ± 8.5 years, 65% women) with T2DM, several sEH-derived fatty acid diols, but not IL-6, were higher among those with a depressive episode (effect sizes up to d = 0.796 for 17, 18-DiHETE, a metabolite of eicosapentaenoic acid [EPA]; t = 2.516, p = 0.016). Among people with a depressive episode, two epoxides were correlated with lower BDI-II scores: 12(13)-EpOME (ρ = −0.541, p = 0.014) and 10(11)-EpDPE (ρ = −0.444, p = 0.049), metabolites of linoleic acid and docosahexaenoic acid (DHA), respectively, while the ratio of 12, 13-DiHOME/12(13)-EpOME was correlated with higher BDI-II scores (ρ = 0.513, p = 0.021). Conclusions: In people with T2DM, major depressive episodes and depressive symptom severity were associated with an oxylipin profile consistent with elimination of pro-resolving lipid mediators by sEH. Highlights: Oxylipin mediators are perturbed in type 2 diabetes mellitus (T2DM). Soluble epoxide hydrolase (sEH)-derived diols were elevated in depressed T2DM patients. Lower cytochrome P450 (CYP450)-derived epoxides were linked to greater depression severity. Disruptions in the CYP450-sEH pathway were related to depressive episodes in people with T2DM.